The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1590/s2175-97902022e20458
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, impact, and management perception of dysmenorrhea among university students: A cross-sectional study

Abstract: Dysmenorrhea is a common condition among females that is characterized by painful cramps before or during menstruation. It is considered as a common gynecological complaint that affects the quality of women's life. The study evaluated prevalence of dysmenorrhea, its impact, associated risk factors, and the management strategies adopted by female university students in Taif city, Saudi Arabia. A cross-sectional study was conducted among 562 female students aged 18-30 years at the university level. The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 30 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…[9], 60-64% in Ile-Ife [10,11], and 69.8% in Maiduguri [12]. These studies have agreed with our study that dysmenorrhea is prevalent among women in their reproductive years though studies have also been conducted aside Nigeria, and it showed that 85.6% in Kuwait [13],79.4% in Saudi Arabia [14], 84.2% in India [15],74.8% in Spanish [16] 89.4% in Al-Asadi, [23] 84.2% in Lithuania [24], 88% in Australia [25], 85.1% in Palestine [26], 83.6% in Northern Ghana [27] and 84.1% in Italy [28], 68.7% in China [29], 74.8% in Spain [16], 94% in Oman [30], 98.4% in Iran [31] and 95% in Turkey [32], 80.9% in Lebanon [17] and 92% in Riyadh [18]. Our findings agree with the findings of these studies that dysmenorrhea abounds in women in their reproductive years.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…[9], 60-64% in Ile-Ife [10,11], and 69.8% in Maiduguri [12]. These studies have agreed with our study that dysmenorrhea is prevalent among women in their reproductive years though studies have also been conducted aside Nigeria, and it showed that 85.6% in Kuwait [13],79.4% in Saudi Arabia [14], 84.2% in India [15],74.8% in Spanish [16] 89.4% in Al-Asadi, [23] 84.2% in Lithuania [24], 88% in Australia [25], 85.1% in Palestine [26], 83.6% in Northern Ghana [27] and 84.1% in Italy [28], 68.7% in China [29], 74.8% in Spain [16], 94% in Oman [30], 98.4% in Iran [31] and 95% in Turkey [32], 80.9% in Lebanon [17] and 92% in Riyadh [18]. Our findings agree with the findings of these studies that dysmenorrhea abounds in women in their reproductive years.…”
Section: Resultssupporting
confidence: 91%
“…The present study revealed that the prevalence of dysmenorrhea was higher among female students who had a family history of dysmenorrhea (74.5%). Similar results were disclosed in a study that reported inconsistent with 65.6% and 60.7% of the students had a family history of dysmenorrhea by El-Mawgod et al [33] and Ali et al [14] respectively. Though our study claims that 30% experienced mild pain, 33% had moderate pain, and 37% had severe pain.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Meanwhile, 194 female students had no family history of dysmenorrhea. In a study by Unsal et al [44], the prevalence of female students with a family history of dysmenorrhea was 295 (47.4%). Based on the chi-square test results, there is a relationship between family history and the incidence of primary dysmenorrhea at the Medical Faculty of UKI.…”
Section: Resultsmentioning
confidence: 96%
“…Dysmenorrhea is characterized by painful spasms before or during menstruation due to cyclic shedding of the inner lining of the uterus. Approximately 34 % of women rated the pain as 7-10 points on the VAS scale (visual analog scale) [35], which negatively affects the intellectual abilities and psychosocial existence of a significant number of adolescent girls and young women [36,37].…”
Section: огляди літератури / Literature Reviewsmentioning
confidence: 99%